Diffuse large B-cell lymphoma—who should we FISH? - Stephens, Deborah M.; Smith, Sonali M. (Annals of Lymphoma, 2018)
Thepoor prognosis and adverse outcomes following standard chemoimmunotherapy forpatients with high-grade B-cell lymphomas harboring rearrangements of MYCand BCL2 and/or BCL6 (HGBL-DH/TH) is now well-established, withless than 20% estimated long term survival following standard therapies.Fortunately, the frequency of HGBL-DH/TH in unselected aggressive B-celllymphomas is relatively uncommon and estimated at 10% of all cases. Thesedouble- and/or triple-hit lymphomas are often, but not universally, associatedwith a clinically aggressive presentation, high-grade morphologic features, orincreased protein expression of the corresponding genes. However, a substantialnumber of patients have no clear indicators of underlying DH/TH. The paradox ofan exceedingly poor prognosis coupled with a relatively uncommon frequencyraises the practical challenge of determining which patient warrants FISHtesting and is an area of substantial controversy and emerging data. Theclinical consequence of missing HGBL-DH/TH is dire, as these patients arelikely undertreated by standard chemoimmunotherapy (RCHOP). However, in acost-conscious era, routine and widespread testing for biologic determinants ofoutcome may not be appropriate, and a critical appraisal of predictors iswarranted. This review will discuss the clinical implications of theserearrangements in aggressive B-cell lymphomas and the potential clinical, pathologic,or biologic predictors of underlying HGBL-DH/TH biology.